Internet of Things Based Employee Presence System Model Using the Agile Method - Abdul Robi Padri; Maryanto Maryanto; Henderi Henderi (Journal of World Science, 2026)
PT Syntax Corporation Indonesia operates in the F&B sector and requires a computerized employee attendance information system to provide precise, fast, and accurate information. The attendance process and recap calculations are still performed manually, which is time-consuming. With a computerized system, this research aims to analyze an Internet of Things–based employee presence system model using Agile methods. The method used to design and analyze the system’s advantages and disadvantages is the Agile methodology. The development flow is as follows: (1) Definition of Requirements, (2) Design, (3) Coding, (4) Testing, and (5) Operation and Maintenance. The results of this study indicate that the information system can minimize employee fraud in manipulating attendance and make it easier for institutions or companies to obtain detailed employee attendance and departure information. The implementation of an Internet of Things (IoT)–based employee presence system is an effort to facilitate employees in recording attendance and generating employee attendance reports. Based on tests and surveys on the use of an Internet of Things (IoT)–based presence system, it achieved an average usability of 79.16%, efficiency of 83.78%, and portability of 74.33%. The use of an Internet of Things (IoT)–based employee attendance system can simplify the attendance process, record employee attendance data, and reduce the risk of losing paper-based attendance records. This system can also improve the overall effectiveness and efficiency of attendance management through automation.